The Comparison between Listening to Al-Quran and Listening to Classical Music on the Brainwave Signal for the Alpha Band - Zulkurnaini, Noor Ashikin; Kadir, Ros Shilawani S. Abdul; Murat, Zunairah Hj; Isa, Roshakimah Mohd (2012 Third International Conference on Intelligent Systems Modelling and Simulation, 2012)
This research investigates and compares the effects of listening to Al-Quran and classical music on human brain wave using EEG. The EEG signal was recorded for three states, which are before, during and after listening to Al-Quran and classical music. 28 healthy participants were randomly chosen among Universiti Teknologi MARA students with age range 20 to 28 years old. During this experiment, each sample was exposed to surah Yasin of Al-Quran and Pachelbel's Canon D major of classical music. Interview sessions were carried out prior to the EEG signals acquisition. Results in terms of correlation between the left and the right brainwaves show that there are increment of 12.67% during listening to A1-Quran and the increment for classical music stands at 9.96%. This finding indicates that listening to the Al-Quran recitation increases the alpha band more than listening to the classical music. Consequently, listening to Al-Quran in particular can result in a more relaxing and alert condition compared to classical music.